FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN PROPERTY & REAL ESTATE - Prasetya, Billy; Santioso, Linda (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to analyze the effect of leverage, Profitability, Liquidity, and Capital Expenditure on cash holding in the property and real estate industry listed on the Indonesia Stock Exchange during 2019-2021. The sampling method used in this research was the purposive sampling method with a total of 36. Data processing techniques using multiple regression analysis helped by E-views 12 and Microsoft Excel 2019. The results of this study indicate that leverage, profitability, and Capital Expenditure have no effect on cash holding, and liquidity has a positive effect on cash holding. The implication of this study is to show that a significant work for a company, is to be fully aware of the amount of cash holding in order to avoid bankruptcy.